2004
DOI: 10.1073/pnas.0307294101
|View full text |Cite
|
Sign up to set email alerts
|

Chronic restraint stress up-regulates GLT-1 mRNA and protein expression in the rat hippocampus: Reversal by tianeptine

Abstract: Excitatory amino acids play a key role in stress-induced remodeling of dendrites in the hippocampus as well as in suppression of neurogenesis in the dentate gyrus. The regulation of extracellular glutamate levels has been suggested as a potential mechanism through which repeated stress causes dendritic remodeling of CA3 pyramidal neurons. Accordingly, the current study examined the distribution and regulation of the glia glutamate transporter GLT-1 and the recently identified GLT isoform, GLT-1b, in the hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
134
3
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(160 citation statements)
references
References 43 publications
(68 reference statements)
13
134
3
10
Order By: Relevance
“…The deficit in ED set shifting seen in the present study after CUS is consistent with a recent report , published as the current work was in preparation, in which a similar deficit in attentional set shifting was seen following repeated restraint stress, a model proposed to induce some of the pathological changes underlying affective disorders (McEwen, 2003;Reagan et al, 2004). In addition to the cognitive deficit, Liston et al (2006) also reported that repeated restraint stress induced apical dendritic atrophy of prefrontal cortical pyramidal neurons, in replication of previous studies (Radley et al, 2004.…”
Section: Discussionsupporting
confidence: 92%
“…The deficit in ED set shifting seen in the present study after CUS is consistent with a recent report , published as the current work was in preparation, in which a similar deficit in attentional set shifting was seen following repeated restraint stress, a model proposed to induce some of the pathological changes underlying affective disorders (McEwen, 2003;Reagan et al, 2004). In addition to the cognitive deficit, Liston et al (2006) also reported that repeated restraint stress induced apical dendritic atrophy of prefrontal cortical pyramidal neurons, in replication of previous studies (Radley et al, 2004.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, chronic restraint stress was associated with an increase in GLT1 mRNA and protein levels in the CA3 region of the hippocampus that was reversible by administration of the antidepressant tianeptine. 83 In contrast, GLT1b was regulated only at the protein level in several hippocampal subfields and the effects were not altered by tianeptine. GLT1 expression is also regulated by glucocorticoids including corticosterone and the synthetic molecule dexamethasone.…”
Section: Mood and Anxiety Disordersmentioning
confidence: 92%
“…NLGN-1 has a key role in the functioning of excitatory synapses and NLGN-2 has a similar role at inhibitory synapses 202 . Alterations in the neural E/I balance 203,204 are believed to underlie social deficits in psychiatric disorders, and chronic stress was shown to lead to an increase in the E/I balance 205,206,207 in the hippocampus of rodents. Chronic stress reduces NLGN-2, but not NLGN-1, expression throughout the hippocampus in parallel with decreased sociability and increased aggression in rats 13 [ figure, part c].…”
Section: Box 4 Stress Cell Adhesion Molecules and The Balance Excitmentioning
confidence: 99%